Multidimensional Assessment of Giftedness: Criterion Validity of Battery of Intelligence and Creativity Measures in Predicting Arts and Academic Talents - Nakano, Tatiana de Cassia; Primi, Ricardo; Ribeiro, Walquiria de Jesus; Almeida, Leandro S. (Anales de Psicología / Annals of Psychology, 2016)
We test the utility of the Battery for Giftedness Assessment (BaAH/S) in identifying differences in two groups of already known gifted students in the areas of academic and artistic talents. Four latent factors were assessed (a) fluid intelligence, (b) metaphor production (verbal creativity), (c) figural fluency (figural creativity), and (d) divergent thinking figural task quality (figural creativity). A sample of 987 children and adolescents, 464 boys and 523 girls, of ages ranging from 8 to 17 of two groups: regular students (N=866) and gifted students (N= 67 academic abilities, N=34 artistic abilities and N=20 no domain identified). Academic giftedness group of have higher reasoning, can produce more remote/original metaphors, high figural fluency and drawings rated as more original. Children in the group of artistic giftedness have higher reasoning, high figural fluency and drawings rated as more original. Reasoning abilities are relatively higher in academic giftedness group than artistic (r = .39 vs r =.14). Within artistic group figural fluency and ratings of originality are relatively more important than reasoning (r = .25 and r = .21 vs .14). We emphasizes the importance of assessing creativity in different domains in addition to intelligence to improve the understanding of giftedness and talent.